Karakterisasi Sifat Fisis dan Mekanis Komposit Berbahan Sabut Lontar dalam Aplikasi Papan Partikel - Syamsuddin, Sahara; Kusmiran, Amirin; Fajar, Fajar; Apriliah, Risky (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2024)
This research used the natural fiber of the Palmyra fruits for composite particle manufacturing, and the physical and mechanical properties were studied on these composite particles. Raw material manufacturing uses the hand lay-up technique with a uniform volume fraction and random fiber in the composite. The presentations of the ratio composition of both fibers of palmyra fruits and epoxy resin are 75:25 for sample A, 70:30 for sample B, 65:35 for sample C, 60:40 for sample D, and 55:45 for sample E. This research shows that densities of the sample A to sample E are in range 0.47 g/cm3 to 0.60 g/cm3, and a sample A has the highest development thickness, with 72.61%, and the lowest is in sample C, with 33.11 %. Water content testing shows that samples A, B, C, and E have range 2.75 % to 7.52 %, and sample D is 17.30 %. For modulus of rapture (MOR), sample A has higher MOR than sample B, C, D, and E. Whereas sample D has lower MOR than the other samples. Sample C has the highest value for modulus of elasticity (MOE), 5526.47 kg/cm2. This sample’s high modulus of elasticity correlates with the percentage of thickness development where the percentage of thickness development of sample C is lowest at 33.11%. The analysis results with AND or OR logic show that samples A, B, and D does not match SNI 03-2105-2006 standards while C and E samples match with SNI 03-2105-2006 standards. Thus, the three samples are not recommended for development. While C and E samples can be developed into particle board by reducing moisture content and improving elasticity properties.